Role of NODDI in the MRI Characterization of Hippocampal Abnormalities in Temporal Lobe Epilepsy: Clinico-histopathologic Correlations. (26th April 2022) - Giachetti, Isabella; Padelli, Francesco; Aquino, Domenico; Garbelli, Rita; De Santis, Dalia; Rossini, Laura; Deleo, Francesco; Pascuzzo, Riccardo; Coras, Roland; Marucci, Gianluca; Tringali, Giovanni; Maccagnano, Carmelo; et al.
Abstract : Background and Objectives: The identification of possible hippocampal alterations is a crucial point for the diagnosis and therapy of patients with unilateral temporal lobe epilepsy (TLE). This study aims to investigate the role of neurite orientation dispersion and density imaging (NODDI) compared to diffusion tensor imaging (DTI) in the comprehension of hippocampal microstructure in TLE. Methods: DTI and NODDI metrics were calculated in the hippocampi of adult patients with TLE, with and without histology-confirmed hippocampal sclerosis (HS), and in age/sex-matched healthy controls (HC). Diffusion metrics and hippocampal volumes of the pathologic side were compared within participants and between participants among the HS, non-HS, and HC groups. Diffusion metrics were also correlated with hippocampal volume and patients' clinical features. After surgery, hippocampal specimens were processed for neuropathology examinations. Results: Fifteen patients with TLE (9 with and 6 without HS) and 11 HC were included. Hippocampal analyses resulted in a significant increase in fractional anisotropy (FA) and mean diffusivity (MD; mm 2 /s × 10 −3 ) and decrease in orientation dispersion index (ODI) comparing the pathologic side of patients with HS and their relative nonpathologic side (0.203 vs 0.183, 0.825 vs 0.724, 0.366 vs 0.443, respectively), the pathologic side of patients without HS (0.203 vs 0.169, 0.825 vs 0.745, 0.366 vs 0.453, respectively), and HC (0.203 vs 0.172, 0.825 vs 0.729, 0.366 vs 0.447, respectively). Moreover, neurite density (ND) was significantly decreased comparing both hippocampi of patients with HS (0.416 vs 0.460). A significant increase in free-water isotropic volume fraction (fiso) was found in the comparison of pathologic hippocampi of patients with HS and nonpathologic hippocampi of patients with HS (0.323 vs 0.258) and HC (0.323 vs 0.226). Hippocampal volume of all patients with TLE negatively correlated with MD ( r = −0.746, p = 0.0145) and positively correlated with ODI ( r = 0.719, p = 0.0145). Fiso and ND of sclerotic hippocampi positively correlated with disease duration ( r = 0.684, p = 0.0424 and r = 0.670, p = 0.0486, respectively). Immunohistochemistry in sclerotic hippocampal specimens revealed neuronal loss in the pyramidal layer and fiber reorganization at the level of stratum lacunosum-moleculare, confirming ODI and ND metrics. Discussion: This study shows the capability of diffusion MRI metrics to detect hippocampal microstructural alterations. Among them, ODI seems to better highlight the fiber reorganization observed by neuropathology in sclerotic hippocampi.